Mast cells contribute to the induction of ocular mucosal alloimmunity. Issue 3 (24th September 2018) - Li, Mingshun; Mittal, Sharad K.; Foulsham, William; Amouzegar, Afsaneh; Sahu, Srikant K.; Chauhan, Sunil K.
Abstract : Beyond their historical role as the effector cells in allergic disorders, mast cells have been implicated in regulating both innate and adaptive immune responses. Possessing considerable functional plasticity, mast cells are abundant at mucosal surfaces, where the host and external environments interface. The purpose of this study was to evaluate the contribution of mast cells to allograft rejection at the ocular surface. Using a well‐characterized murine model of corneal transplantation, we report that mast cells promote allosensitization. Our data show mast cell frequencies and activation are increased following transplantation. We demonstrate that mast cell inhibition (a) limits the infiltration of inflammatory cells and APC maturation at the graft site; (b) reduces allosensitization and the generation of Th1 cells in draining lymphoid tissues; (c) decreases graft infiltration of alloimmune‐inflammatory cells; and (d) prolongs allograft survival. Our data demonstrate a novel function of mast cells in promoting allosensitization at the ocular surface. Abstract : This investigation provides new insights into the role of mast cells in promoting induction of transplant immunity and demonstrates that inhibition of mast cell function leads to decreased maturation of antigen‐presenting cells, reduced generation of type 1 T helper cells, and delayed graft rejection.